Ferrovia Norte-Sul e os impactos econômicos dos terminais multimodais nos municípios do tramo norte - Oliveira, Lourdes Antônia da Silva (2021)
This dissertation seeks to analyze the importance of the integration terminals of the North Section of the North-South Railway (FNS) for the economic development of the municipalities of Açailândia (MA) and Porto Franco (MA) and the municipalities of Palmeirante (TO) and Porto Nacional (TO) In this scenario, the North-South Railway, although it was not designed to transport passengers, is an important corridor that allows the flow of grains, idealized in the 1980s, it shows itself as a possibility of integration between the Brazilian regions, both from North to South and from West to East, when completed, it will have an extension of 4,155 kilometers in length. The general objective of this research was to analyze the relevance of the railway modal for the country, its influence for the growth and economic development of the municipalities that received the multimodal yards, located in the North section of the North-South Railway. Another aspect highlighted, is the influence and importance of the infrastructure, giving emphasis to railroads in productive agglomerations, in the light of François Perroux's theory of Growth Poles, seeking to understand the dynamics of economic activity in spaces and their impacts on poles and regions. As for the methodology, a literature review, documentary research, reading, analysis and interpretation of data provided by the Brazilian Institute of Geography and Statistics (IBGE, acronym in Portuguese) and the Institute for Applied Economic Research (IPEA, acronym in Portuguese) were carried out. Through the researched data, it seeks to show possible impacts of the FNS on the growth and development of the mentioned municipalities, located in the Northern section of the Railway, based on variables related to agribusiness, industry, average wages, employability, GDP, GDP per capita and the Municipal Service Tax (ISSQN, acronym in Portuguese) of such municipalities. Data were collected from these sectors, after analysis, their measurement occurred through the elaboration of graphs and tables, which show an increase in the variables of the analyzed period. It also demonstrates how public / private management is an alternative for the consolidation of Brazilian railways, contributing to interconnect and intensify the economic relationship between municipalities and regions of the country with the world market. Since the North section of FNS, is fully operational, under the responsibility of the concessionaire Valor Logística Integração (VLI)